(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Ready-to-eat products of chickpea are rich in energy and various macro and micronutrients and eaten as such. A variety of sweet and savoury ready-to-eat chickpea products are available in the market and consumed all over India due to its excellent flavour and taste. Aim: The present study was planned to assess the nutritive value of ready–to-eat products of chickpea available locally. Methods and Material: Four products, roasted chickpea - with and without husk, roasted spiced chickpea, and Chana zor garam were procured from the local market of Jaipur city. Standard techniques given by AOAC were used to assess moisture, total ash, total fat, crude fibre, crude protein, total carbohydrates, total fat, calcium and iron content. Results and Conclusion: The average energy content of the four types of roasted products of chickpea studied ranged from 369.05±3.8235 to 388.30±6.2283 kcal, while protein and total fat contents ranged from 16.05±1.935 to 21.22±1.937 3.95±0.91 to 8.50±1.3977 g/100g respectively. The mean carbohydrate and fibre contents ranged from 60.50±3.2850 to 64.19±1.3261 g and 0.77±0.1345 to 1.0±0.2479 g respectively. The iron content ranged between 5.09±0.3021 and 9.76±0.565 mg/100g. The iron content ranged between 5.09±0.3021 and 9.76±0.565 mg/100g. The sodium and potassium values ranged from 56.6 to 194 mg/100g and 856 to 1375 mg/100g respectively. The antinutrient phytic acid ranged from 156.5±3.473 to 165.0±7.40 mg/100g. Thus, the ready-to-eat products of chickpea are affordable good options for nutritionally rich any-time snacks providing high energy, protein and micronutrients particularly.